Pengembangan Permainan Kanya Sebagai Media Pembelajaran Materi Kalimat Tanya Siswa Kelas 3 SD 6 Gondangmanis - Ananta, Agti Fiana Qairul; Khairani, Fenita; Andriyani, Risa; Setiawaty, Rani (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to achieve two objectives. First, to develop the KANYA media as a learning tool for interrogative sentence materials in the Indonesian language subject. Second, to evaluate the effectiveness of this media. The research method adopts the Research and Development ADDIE model, involving analysis, design, development, implementation, and evaluation stages. The research subjects consist of 7 third-grade students (4 male and 3 female) at SD 6 Gondangmanis, Bae, Kudus. Data collection is done through observation, interviews, and response questionnaires from teachers and students. The research effectiveness is evaluated using a pre-test and post-test design for a single group. The obtained data are analyzed qualitatively and quantitatively, using assessment criteria to determine the suitability of the product. The results of this study show that first, the KANYA media has been successfully developed with a score of 4.8 from media experts and 4.3 from subject matter experts, indicating a high level of suitability. Second, both teachers and students responded positively to the KANYA media, with scores of 4.5 and 4.9, respectively. Furthermore, there was an improvement in student understanding from the pre-test (53.05%) to the post-test (74.85%), indicating an increase of 31.38%. Thus, the KANYA media is effectively used as a learning tool for interrogative sentence materials in the third grade at SD 6 Gondangmanis.